Prevalence of chronic kidney disease in Peruvian primary care setting. - Herrera-Añazco, Percy (2017)
Background: Chronic Kidney Disease (CKD) is a worldwide public health problem. There are few studies in Latin America, especially in primary care settings. Our objective was to determine the prevalence, stages, and associated factors of CKD in primary care setting. Methods: We did a retrospective secondary analysis of a database from the Diabetes and Hypertension Primary Care Center of the Peruvian Social Security System (EsSalud) in Lima, Peru. We defined CKD as the presence of eGFR <60 mL/min and/or albuminuria >30 mg/day in 24 h, according to Kidney Disease: Improving Global Outcomes (KDIGO). Factors associated with CKD were evaluated with Poisson Regression models; these factors included age, gender, type 2 diabetes mellitus (DM2), hypertension (HTN), body mass index (BMI), and uric acid. Associations were described as crude and adjusted prevalence ratios (PR) and their 95% confidence intervals (95% CI). Results: We evaluated 1211 patients (women [59%], mean age 65.8 years [SD: 12.7]). Prevalence of CKD was 18%. Using the estimated glomerular filtration rate (eGFR), the prevalence was 9.3% (95% CI 5.3 – 13.3) in patients without HTN or DM2; 20.2% (95% CI 17.6 – 22.8) in patients with HTN, and 23.9% (95% CI 19.4 – 28.4) in patients with DM2. The most common stages were 1 and 2 with 41.5% and 48%, respectively. Factors associated with CKD in the adjusted analysis were: age in years (PR = 1.03, 95% CI 1.01 – 1.04), DM2 (PR = 3.37, 95% CI 1.09 – 10.39), HTN plus DM2 (PR = 3.90, 95% CI 1.54 – 9.88), and uric acid from 5 to <7 mg/dL (PR = 2.04, 95% CI 1.31 – 3.19) and ≥7 mg/dL (PR = 5.19, 95% CI 3.32 – 8.11). Conclusions: Prevalence of CKD in the primary care setting population was high. CKD is more frequent in the early stages of the disease, and individuals with hypertension, DM2, older age and hyperuricemia have higher prevalence of CKD.